GLI1 expression in pancreatic ductal adenocarcinoma correlates the clinical significance and prognosis: A meta-analysis. Issue 26 (26th June 2020) - Li, Ruidan; Liu, Zheran; Chen, Ye; Hu, Xiaolin; Peng, Xingchen
Abstract: Background: Glioma-associated oncogene homolog 1(GLI1) expression correlates with the clinical significance and prognosis of several cancers. However, the evaluation of the role GLI1 expression plays in pancreatic ductal adenocarcinoma (PDAC) clinicopathological features and outcomes still lacks. Objective: The present study systemic reviewed the association of GLI1 expression and clinical significance as well as patients survival in PDAC. Methods: We systematically searched the database of The Cochrane Library, PubMed, Embase, CNKI, Weipu data, and Wanfang data according to the inclusion and exclusion criteria. (The search ended on January 1, 2019; no language restrictions). The Newcastle-Ottawa Scale (NOS) scale was implemented to assess the quality of the literature and the Review Manager 5.3 Software was used to conduct a meta-analysis. Finally, 9 studies, a total of 1058 patients, have been included. Results: GLI1 is more likely expressed in PDAC tissue rather than para-carcinoma tissue (OR = 2.86, 95%CI = 1.87–4.36, P  < .00001). GLI1 expression is associated with the TNM stage (OR = 3.11, 95%CI = 2.01–4.79, P  < .00001), perineural invasion (OR = 2.50, 95%CI = 1.28–4.91, P  = .008), and lymphatic metastasis (OR = 2.73, 95%CI = 1.71–4.36, P  < .0001). But the association with differentiation (OR = 1.20, 95%CI = 0.74–1.96, P  = .46) and tumor size (OR = 2.41, 95%CI = 0.97–6.00, P  = .06) was not significant. GLI1 expression is related to the worse overall survival in PDACs (HR = 1.68, 95%CI = 1.40–2.02, P  < .00001). Conclusion: Positive GLI1 expression promotes the progression and metastasis of PDACs and plays an important role in the clinical significance and the patients survival. Abstract : Supplemental Digital Content is available in the text